Disability is not a taboo but a competitive disadvantage for leadership: a construction of Asante and Gonja cultures in Ghana - James Kwabena Bomfeh; John Victor Mensah; David Wellington Essaw (Cogent Social Sciences)
There is a widespread belief that disability is a taboo for leadership culturally in Ghana. However, there is little empirical evidence to support this belief. The present study, therefore, explored the disability and leadership construction of Ghana, particularly in Asante and Gonja cultures. This study evokes life course and social constructionist theories. Adopting a qualitative research approach, critical ethnography and narratives were used to conduct the study. Six participants were included in this study. In-depth interviews and interview guides were used as data collection methods and instruments. Critical discourse analysis and life reviews were used to analyze the data. Among the findings were that there are varied cultural constructions of disability and leadership, typically that disability is not a taboo but a competitive disadvantage to leadership, contrary to widely held views. This study contributes critical ethnography and narrative as qualitative research designs to the discourse on disability and development in sync with all the seventeen (17) Sustainable Development Goals of inclusion emphasizing on the inclusion of all persons.